Teaching of English as a Factor of Speech Intensification of Pre-School Children - Olga Boyko (Pedagogical Discourse, 2012)
Communicative competence as the final aim of speech activity of pre-school children is analyzed in the article. The problem of bilingualism of pre-school children in scientific works of Ukrainian and foreign authors is discussed.